2013
DOI: 10.1148/radiol.13121441
|View full text |Cite
|
Sign up to set email alerts
|

Myocardium: Dynamic versus Single-Shot CT Perfusion Imaging

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.13121441/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 26 publications
2
66
1
2
Order By: Relevance
“…18 Our study also showed that the time point of maximal enhancement was later and the peak CT attenuation was lower in ischemic myocardium, compared with normal myocardium. Among the 11 series of single-phase CTP images, the singlephase CTP image acquired at 2-6 s from Tmax in the ascending aorta had high accuracy for detecting myocardial ischemia and was comparable to dynamic CTP.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…18 Our study also showed that the time point of maximal enhancement was later and the peak CT attenuation was lower in ischemic myocardium, compared with normal myocardium. Among the 11 series of single-phase CTP images, the singlephase CTP image acquired at 2-6 s from Tmax in the ascending aorta had high accuracy for detecting myocardial ischemia and was comparable to dynamic CTP.…”
Section: Discussionsupporting
confidence: 69%
“…Huber et al also indicated that single-phase CTP had a similar performance to the dynamic CTP in the detection of myocardial ischemia if the single-phase CTP was acquired at the optimal scan time. 18 This optimal time period is also beneficial when using 64-slice CT to obtain single-phase CTP images at suboptimal scan timing. However, the optimal scan time may vary substantially according to each case, because the Tmax in the ascending aorta is not necessarily always the same, and it is difficult to determine the optimal scan timing using a conventional bolus tracking technique.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of prior work evaluates the ability of CT myocardial perfusion assessment to identify physiologically significant epicardial disease. 5,10,11,[21][22][23] Several studies have shown that CT perfusion can improve the specificity and positive predictive value of CT angiography (for static, 23 and for dynamic 10,11 ). However, not all perfusion defects are linked to a focal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In one notable exception, Huber et al 5 directly compared dynamic and static performance for the detection of hemodynamically relevant coronary stenoses. Consistent with our findings, these authors concluded that static and dynamic methods have similar detection performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation